2022
DOI: 10.1002/mp.15486
|View full text |Cite
|
Sign up to set email alerts
|

Time structure of pencil beam scanning proton FLASH beams measured with scintillator detectors and compared with log files

Abstract: Purpose Key factors in FLASH treatments are the ultra‐high dose rate (UHDR) and the time structure of the beam delivery. Measurement of the time structure in pencil beam scanning (PBS) proton FLASH treatments is challenging for many types of detectors since high temporal resolution is needed. In this study, a fast scintillator detector system was developed and used to measure the individual spot durations as well as the time when the beam moves between two positions (transition duration) during PBS proton FLAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 30 publications
0
25
0
Order By: Relevance
“…For all irradiations, the duration of each spot delivery was extracted from machine log files [24]. The field dose rate was determined as the total dose divided by the total field duration.…”
Section: Dose Deliverymentioning
confidence: 99%
“…For all irradiations, the duration of each spot delivery was extracted from machine log files [24]. The field dose rate was determined as the total dose divided by the total field duration.…”
Section: Dose Deliverymentioning
confidence: 99%
“…Among the available scintillators, ZnSe:O is promising for future investigation being characterized by ultra-fast decay, high LO and radiation tolerance. The Aarhus University group in Denmark recently showed that ZnSe:O crystals can be successfully used for measurements of the time structure of FLASH pencil scanning proton beams with a dosimetry setup similar to the one proposed in this work 27 . The results reported in Figure 6 show that the proposed detection system provides beam profile measurements at sub-millimeter level 28 .…”
Section: Discussionmentioning
confidence: 98%
“…Favaudon et al [35] tested a commercial device based on an inorganic scintillator for electron beams relative dosimetry in the (0.4-3.5×10 6 ) Gy/s range with good results. Kanouta et al [34] made use of small volume inorganic scintillators to measure the time structure of PBS proton deliveries up to 92.5 Gy/s, but a dose rate response characterization was not in the scope of their work. Our data show that the sensitivity change of Gd d O 2 S:Tb crystals is limited to a maximum of 3 % in the investigated range.…”
Section: Discussionmentioning
confidence: 99%
“…Inorganic scintillators coupled with cameras or photomultipliers have been largely used in conventional radiotherapy [31][32][33]. Their application to the UHDR regime has been limited so far and to our knowledge to relative [9,11] or time resolved [34,35] measurements. In our study, we aimed at testing the dose rate response of an in-house developed system based on Gd d O 2 S:Tb scintillator up to 2220 Gy/s.…”
Section: Introductionmentioning
confidence: 99%